A new potentially toxic Azadinium species (Dinophyceae) from the Mediterranean Sea, A. dexteroporum sp. nov. Issue 5 (27th August 2013) - Percopo, Isabella; Siano, Raffaele; Rossi, Rachele; Soprano, Vittorio; Sarno, Diana; Zingone, Adriana; De, O.
<x xml:space="preserve">Abstract</x> A new photosynthetic planktonic marine dinoflagellate, Azadinium dexteroporum sp. nov., is described from the Gulf of Naples (South Tyrrhenian Sea, Mediterranean Sea). The plate formula of the species, Po, cp, X, 4′, 3a, 6″, 6C, 5?S, 6‴ and 2″″, is typical for this recently described genus. Azadinium dexteroporum is the smallest rep‐resentative of the genus (8.5 μm average length, 6.2 μm average width) and shares the presence of a small antapical spine with the type species A. spinosum and with A. polongum. However, it differs from all other Azadinium species for the markedly asymmetrical Po plate and the position of the ventral pore, which is located at the right posterior end of the Po plate. Another peculiarity of A. dexteroporum is the pronounced concavity of the second intercalary plate (2a), which appears collapsed with respect to the other plates. Phylogenetic analyses based on the large subunit 28S rDNA (D1/D2) and the internal transcribed spacer (ITS rDNA) support the attribution of A. dexteroporum to the genus Azadinium and its separation from the other known species. LC/MS‐TOF analysis shows that Azadinium dex‐teroporum produces azaspiracids in low amounts. Some of them have the same molecular weight as known compounds such as azaspiracid‐3 and ‐7 and Compound 3 from Amphidoma languida, as well as similar fragmentation patterns in some cases. This is the first finding of a species producing azapiracids in the Mediterranean Sea.